Implementation of 5S, SLP, standard work, ABC and minimum and maximum system in a warehouse in Metropolitan Lima - Valdivia Alfaro, Alberto David (2025)
The current research focuses on the examination of a mid-sized company involved in the sale of motorcycle spare parts, with a primary concern revolving around the notably low percentage of On Time In Full (OTIF) orders. While the industry standard for OTIF orders stands at 69%, the company’s performance lags behind at approximately 54%. After a thorough diagnosis, the bottleneck in the process was pinpointed in the packing department, where operatives took an extended duration to pack products for subsequent delivery. The estimated economic impact of this inefficiency was approximately $41,504. In response to this challenge, an improvement model was implemented, incorporating tools such as 5S, Systematic Layout Planning, Standard Work, ABC Classification, and Minimums and Maximums System to optimize inventory distribution, stock management, and warehouse cleanliness. The positive outcomes were realized through the utilization of Arena software and the available space provided by the company to implement these changes within its premises. Furthermore, an economic analysis of the Project involved a sensitivity analysis using the @Risk tool in Microsoft Excel to assess the profitability of the proposed enhancements for the company.